2014
DOI: 10.1038/jhh.2013.140
|View full text |Cite
|
Sign up to set email alerts
|

Apparent and true resistant hypertension: definition, prevalence and outcomes

Abstract: Resistant hypertension, defined as blood pressure (BP) remaining above goal despite the use of ≥3 antihypertensive medications at maximally tolerated doses (one ideally being a diuretic) or BP that requires ≥4 agents to achieve control, has received more attention with increased efforts to improve BP control rates and the emergence of device-based therapies for hypertension. This classically defined resistant group consists of patients with true resistant hypertension, controlled resistant hypertension and pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
175
0
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(195 citation statements)
references
References 33 publications
1
175
0
19
Order By: Relevance
“…Nevertheless, their therapeutic effectiveness in lowering BP is well-recognised in the treatment of resistant hypertension (RH). It has been reported that 10.1% of patients treated for elevated BP failed to attain target BP levels despite widespread use of conventional antihypertensive therapy [26]. According to cross-sectional analysis of the United States National Health and Nutrition Examination Survey (NHANES), the prevalence of patients who met the criteria for RH (defined by systolic and diastolic BP ≥ 140/90 mmHg and reported use of three different drug classes or drugs from ≥ four antihypertensive drug classes irrespective of BP levels) has doubled, reaching 11.8% in 2006 compared to 5.5% in the years 1998-2004 [3].…”
Section: Choice Of Antihypertensive Drugsmentioning
confidence: 99%
“…Nevertheless, their therapeutic effectiveness in lowering BP is well-recognised in the treatment of resistant hypertension (RH). It has been reported that 10.1% of patients treated for elevated BP failed to attain target BP levels despite widespread use of conventional antihypertensive therapy [26]. According to cross-sectional analysis of the United States National Health and Nutrition Examination Survey (NHANES), the prevalence of patients who met the criteria for RH (defined by systolic and diastolic BP ≥ 140/90 mmHg and reported use of three different drug classes or drugs from ≥ four antihypertensive drug classes irrespective of BP levels) has doubled, reaching 11.8% in 2006 compared to 5.5% in the years 1998-2004 [3].…”
Section: Choice Of Antihypertensive Drugsmentioning
confidence: 99%
“…The variability of prevalence can be attributed to patient selection and, more importantly, to the capability to rule out pseudoresistance caused by white-coat hypertension, nonadherence and suboptimal dosing. In a recent pooled analysis, prevalence rate of 10.1 % was found for uncontrolled resistant hypertension among individuals treated for hypertension (8).…”
Section: Introductionmentioning
confidence: 99%
“…Uma melhor compreensão da ocorrência e resultados associados à hipertensão resistente e pseudorresistente é importante para melhorar a gestão desses pacientes, possibilitando um melhor tratamento e podendo evitar possíveis danos ao individuo hipertenso (11,12). Este estudo teve como objetivo identificar a HAR e a hipertensão pseudorresistente em pacientes atendidos em uma Unidade de Saúde da Família.…”
Section: Introductionunclassified